Youth lifestyles, digital engagement and political participation – are we measuring it right? - Lai, Che Ching; Hasan, Hamisah; Samsuddin, Jamali (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2017)
This paper aim to highlight some of issues arose in measuring youth lifestyles, digital engagement and political participation. These variables were part of a nationwide survey titled “Youth in the marginalised society: from the Transitional to the Generational approach”. This issue need attention due to the fact that the fast changing technologies are affecting youth lifestyles as well as their digital engagement and political participation. It has never happened before. During the newspapers, radio and television technology, life is very slow. There was a clear demarcation between sources and recipients. However with the web 2.0 technology which allows for users to become producers, it certainly changed the entire media landscape. The changes are affecting youth lifestyles, digital engagement as well as the nature of their political participation hence the question are we measuring it right? Literatures shows that lifestyles can be measured based on three dimensions, namely behaviour, interest and preferences as well as attitudes. However, in the study above, two dimensions namely behaviour and interest were used to measure youth lifestyles. Does measuring youth lifestyle based on two dimensions is right? Further analysis lead to a conclusion that it was possible to measure youth lifestyle based on two dimensions. Internet usage as a variable has been used by most researcher and it was defined mostly in relation to the time spent on-line. However, the recent trend called for more rigorous measurement than time spent online. Hence, the digital engagement variables were developed to measure the youth engagement on the internet. The discussion shows that this variable seems to be measuring what it supposed to measure. The final variable is political participation. The issue about this variable is related to whether its measure the online or the offline political participation. This is because Collins (2008) argued that young people realised internet as a legitimate online political participation. The discussion found that the measurement used in this study to measure political participation was to measure offline political participation. This need to be reviewed as the findings could lead to the wrong conclusion. Asking this simple question of ‘are we measuring it right’ would probably highlight the weaknesses of the existing measurement and provide better understanding of how we could ask the right questions particularly in the context of fast changing environment surrounding the youth.